Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to find $\lim_{x \rightarrow0} (1-3 \cdot x)^{\frac{1}{x}}$

I thought about finding the limit of

$$(1-3 \cdot x)^{\frac{1}{x}}= e^{\frac{\ln(1-3 \cdot x)}{x}}$$

But that only works if $e^{\frac{\ln(1-3 \cdot x)}{x}}$ is continuous at $x=0$, which as far as I understand it is not. Am I right about that? And if I am, how do I find the limit?


share|cite|improve this question
Continuity at $0$ is irrelevant. To use many arguments, we do want the function to be continuous in a deleted neighbourhood of $0$. So there should exist an $\epsilon$ such that the function is continuous at all $x$ such that $0<|x|<\epsilon$. – André Nicolas May 21 '12 at 14:02

Instead of working with $e^{\frac1x\ln(1-3x)}$, work with $\frac{\ln(1-3x)}x$ directly: the hypotheses of l’Hospital’s rule are satisfied, so you can use it to find $$\lim_{x\to 0}\frac{\ln(1-3x)}x=\lim_{x\to 0}\ln (1-3x)^{1/x}=\ln\lim_{x\to 0}(1-3x)^{1/x}\;,$$ and then just exponentiate to get the desired limit.

share|cite|improve this answer

$\lim_{x \rightarrow0} (1-3 \cdot x)^{\frac{1}{x}}$ = $\lim_{x \rightarrow0} ((1+(-3) \cdot x)^{\frac{1}{-3x}})^{{-3}}$ = $e^{{-3}}$

share|cite|improve this answer
Wait but that is only true if $e^{\frac{\ln(1-3x)}{x}}$ is continuous at $x=0$ isn't it? – yotamoo May 21 '12 at 10:06

Hint 1: What happens if you substitute $x=\frac 1n$? You will get a well known series.

Hint 2: One of the definitions of $e^a$ is given by $$e^a=\lim_{n\to\infty}(1+\frac an)^n.$$

share|cite|improve this answer
We haven't really dealt with series's, even though it seems like it converges to 1 as $x \rightarrow 0$ – yotamoo May 21 '12 at 9:55
I added a second hint. Does that help? – Simon Markett May 21 '12 at 10:24

Following the ideas of Simon and Prasad: if you know that $\,\displaystyle{\lim_{x\to\infty}\left(1+\frac{a}{f(x)}\right)^{f(x)}=e^a}\,$ for any function $\,f(x)\,$ s.t. $\,\displaystyle{\lim_{x\to\infty} f(x)=\infty}\,$ , then you're done as $$\lim_{x\to 0}(1-3x)^{1/x}=\lim_{x\to 0}\left(1-\frac{3}{1/x}\right)^{1/x}=e^{-3}$$

share|cite|improve this answer

As above, the limit is $e^{-3}$. Your function doesn't have to be defined at $x = 0$; you're only interested in the limit to which it tends as $x \to 0$.

My workings would look like this:

$$ \begin{eqnarray*} \lim_{x\to 0} (1-3x)^{1/x} &=& \lim_{x\to 0} e^{1/x \ln (1-3x)} \\ &=& e^{\lim_{x\to 0}1/x\ln (1-3x)} \\ &=& e^{\lim_{x\to 0} \frac{\frac{-3}{1-3x}}{1}} \text{ by l'Hospital} \\ &=& e^{-3} \end{eqnarray*} $$

I'm not sure if I'm abusing notation here or if I'm relying on implicit assumptions (maybe the continuity of $e^{x}$ when I take the limit into the exponent?). But this is just how I would work this out for myself.

Hope it helps :-)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.